THE KNOWLEDGE, PRACTICES, AND ATTITUDES OF GENERAL PRACTITIONERS ON IRRITABLE BOWEL SYNDROME AMONG FAMILY PRACTITIONERS - KHAN , AM; KHAN , ZU; BASIT , A; KHAN , MA; ALI , A (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to examine general practitioners' knowledge, practices, and attitudes regarding irritable bowel syndrome (IBS). The study was designed as a cross-sectional study conducted at the Department of Medicine MTI, LRH Hospital Peshawar, between February 2021 and August 2021. A total of 200 general practitioners working in various clinics and hospitals were included in the study. Gastroenterologists and medical experts were excluded. Non-probability convenient sampling was used to select the participants. After obtaining their consent, the participants were asked to complete a questionnaire about their knowledge, practices, and attitudes towards IBS. The data was analyzed using SPSS version 28. Frequencies and percentages were used for categorical data, while mean and standard deviation were used for quantitative data. The Chi-Square test was applied to test the significance of the p-value, which was set at 0.05 or less. The respondents' mean age was 36 years, with an equal male-to-female ratio. More than half of the general practitioners (56%) were from rural regions, while the rest were from metropolitan areas. The knowledge questions were scored using true, false, and don't know options. 43% of respondents believed that IBS is a genetic illness, while 26% disagreed, and 33% were unsure. 51% of respondents thought that only women have IBS, while 33% disagreed, and 20% were unsure. 51% of the participants believed that IBS is a potentially fatal illness, while 27% disagreed, and 22% were unsure. When asked about their practices related to IBS management, 58% said they consistently took the prescribed drugs, while 42% did not. 64% said they avoided gluten-containing foods, while 36% did not. 51% of the respondents said they practiced yoga, while 49% did not. The comments of the participants regarding their views towards IBS were also recorded. A significant correlation was found between the participant's answers to the question, "Do you think your everyday life is less influenced now that you are following your doctor's advice about nutrition, lifestyle, and medications?" (p-value=0.04). The study found that the general practitioners had a sufficient degree of knowledge about IBS, which is essential for proper referral and treatment by qualified medical professionals and subject matter specialists.